2018
DOI: 10.1073/pnas.1810058115
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors are essential constituents of stable and seeding-active tau fibrils

Abstract: Amyloid fibrils are cross-β–rich aggregates that are exceptionally stable forms of protein assembly. Accumulation of tau amyloid fibrils is involved in many neurodegenerative diseases, including Alzheimer’s disease (AD). Heparin-induced aggregates have been widely used and assumed to be a good tau amyloid fibril model for most biophysical studies. Here we show that mature fibrils made of 4R tau variants, prepared with heparin or RNA, spontaneously depolymerize and release monomers when their cofactors are remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 39 publications
(43 reference statements)
8
86
2
Order By: Relevance
“…Meanwhile we observed that the optimal stoichiometry of heparin that facilitates amyloid aggregation is very different from that for LLPS ( Figure 2). This is consistent with the previous observations that tau-polyanion LLPS favors stoichiometry that meets net charge balancing [30], while tau-heparin amyloid aggregation proceeds via a defined molar ratio of tau and heparin, likely mediated by directed conformational templating [49], [50]. The distinct conformation change and optimal stoichiometry suggest these two processes are governed by distinct mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile we observed that the optimal stoichiometry of heparin that facilitates amyloid aggregation is very different from that for LLPS ( Figure 2). This is consistent with the previous observations that tau-polyanion LLPS favors stoichiometry that meets net charge balancing [30], while tau-heparin amyloid aggregation proceeds via a defined molar ratio of tau and heparin, likely mediated by directed conformational templating [49], [50]. The distinct conformation change and optimal stoichiometry suggest these two processes are governed by distinct mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, tau fibrils induced by addition of heparin, the most commonly used cofactor, were found to be heterogeneous and different from brain-extracted fibril structures (Fichou et al, 2018b;Zhang et al, 2019a), thereby questioning the quality of cofactor-induced fibrils as an aggregate model. However, recent studies demonstrated the biological relevance of cofactors in tau aggregation, by indirectly showing its involvement in seeding and fibril stability (Fichou et al, 2018a) and by showing that a cofactor of unknown identity is part of the fibril core in CTE (Falcon et al, 2019) and CBD (Zhang et al, 2019b). Through the study of cofactor-induced aggregation of recombinant tau in vitro, we endeavor to find defining molecular features of aggregation-prone or seeding-competent tau species.…”
Section: Introductionmentioning
confidence: 99%
“…Heparin-induced tau aggregation has been modeled in several quantitative studies (Ramachandran and Udgaonkar, 2011;Shammas et al, 2015;Kjaergaard et al, 2018) and has provided a global picture where heparin interacts with tau to form aggregation competent oligomers that evolve to fibrils. However, even a property as basic as the inclusion of heparin into the mature fibrils is disputed, with multiple conflicting reports saying that heparin is either not part of fibrils (von Bergen et al, 2006;Carlson et al, 2007;Ramachandran and Udgaonkar, 2011) or part of the final aggregate (Sibille et al, 2006;Dinkel et al, 2015;Fichou et al, 2018a). It is perhaps due to these observations that heparin's treatment in literature has largely been that of a useful catalyst rather than a critical reactant.…”
Section: Introductionmentioning
confidence: 99%
“…[9] It includes at least three ESR-based distance measurement techniques, double electron-electron resonance (DEER or PELDOR), doubleq uantum coherence (DQC), and relaxation-induced dipolar modulation enhancement (RIDME), all of which have recently emerged as the methodo fc hoice in the fields of biophysicsa sw ell as molecular and structuralb iology. [7,8,10] They are now routinelyu sed to characterize the conformation ensemble of proteins,w hich is associated with protein dynamics, [4,11] to reveal structural transitions betweendifferentconformations of membrane protein in liposomes or nanodiscs, [12][13][14] and to validate crystal structures in membrane environments. [15] To perform pulsed dipolar measurements, ad oubly spin-labeled protein is generally required and is prepared by the SDSL methodology ( Figure 1A).…”
Section: General Procedures Of Pulsed Dipolar Esr Measurement and Analmentioning
confidence: 99%